Behavioural Insights into Digital Nudge Marketing: A Study of Consumer Behaviour and Digital Literacy in Healthy Food-Related Product Education Contexts - Hesty Nurul Utami; Raihana Nanditha Zaky; Sulistyodewi Nur Wiyono; Dini Turipanam Alamanda; Dwi Novanda Sari; Koblarp Chandrasapth (Postgraduate, University of Mataram, 2025)
The jamu industry, the locally grown healthy beverage industry in Indonesia, embarks on the opportunity to support the consumer food lifestyle. This study examines a company producing Jamu products that uses a digital platform to market its offerings. Fluctuations in purchases have led the company to adopt a Nudge business strategy in its digital content marketing. This study surveys the role of digital nudges on consumers' purchase intentions and decisions regarding Jamu products. Nudging marketing proposes a selling technique by manipulating customer behaviour closer to the deal. This study applies a quantitative approach with a Partial Least Squares-based Structural Equation Modelling (SEM-PLS) method. Data collection techniques were conducted by surveying 124 customers of Jamu products manufactured by a Jamu company based in Bandung City. The results show that nudges do not directly influence purchasing decisions but significantly impact those decisions when mediated by purchase intention. This study contributes to digital marketing and consumer behaviour literature by providing insights into how nudging marketing can be strategically implemented to promote local and healthy food-related products in modern digital business environments.